Still the One. - LINDBERG, TOD (Commentary)
The article focuses on Brendan Simms's analysis of global power competition, foreign policy realism, and the evolving international order in his book The Return of the Great Powers. Topics include rivalry among major powers like the U.S., Russia, and China, geopolitical tensions involving strategic regions and conflicts, and the challenges of understanding future global dynamics.